Two decades of altered snow cover does not affect soil microbial ability to catabolize carbon compounds in an oceanic alpine heath. (September 2018) - Wubs, E.R. Jasper; Woodin, Sarah J.; Stutter, Marc I.; Wipf, Sonja; Sommerkorn, Martin; van der Wal, René
Abstract: Snow strongly affects ecosystem functioning in alpine environments with potential carry-over effects outside of snow periods. However, it is unclear whether changes in snow cover affect microbial community functioning in summer. In a field experiment, we tested whether manipulation of snow cover affected the functional capabilities of the microbial community either directly, or indirectly through concomitant changes in the vegetation. While 23 years of differential snow depth and persistence fundamentally changed the vegetation composition, the microbial community's ability to catabolize a range of carbon compounds was not altered. Instead, soil moisture content was the key driver of carbon catabolism by the microbial community. Highlights: We transplanted plant-soil monoliths near and away from a 20-yr standing snow fence. We found no differences in microbial C functioning due to snow cover or vegetation. Instead, concomitant soil moisture content drove C processing.